The structural modelling of significant organisational and individual factors for promoting sustainable campus in Saudi Arabia - Alsharif, Mohammad Ambarak (Frontiers in Sustainability, 2024)
Introduction In recent years, campus sustainability has gained global prominence, with a focus on sustainability initiatives and environmental activities within university campuses. This study aims to explore the factors contributing to the expansion of sustainability initiatives in Saudi Arabian university campuses. Methods The research utilizes the Interpretive Structural Model (ISM) as a framework for public universities. A literature review incorporating rational choice theory (RCT) and organizational change theory (OCT) is conducted to identify variables relevant to campus sustainability. The hierarchical interrelationships among these variables are examined, and the Matrice d’Impacts Croises-Multiplication Appliqué and Classment Analysis (MICMAC) categorize the study variables. Associations between the variables are validated through expert consultations from selected case study institutions. Results The findings highlight the significance of organizational structure and decision-making processes in determining the prevalence of other sustainability-related variables. Organizational structure and decision-making processes are recognized as key factors exerting significant influence over other variables. Additionally, leadership is categorized as a linkage variable, representing a strong relationship within the hierarchical model. Discussion The study acknowledges the challenges in implementing sustainability initiatives, including conflicts in strategic planning, absence of campus sustainability policies and regulations, financial barriers, and lack of support from leadership. The study offers valuable insights and recommendations for stakeholders involved in sustainability initiatives within higher education institutions, particularly university leaders and decision makers in facility and project management departments (F&PM). By addressing the organizational and decision-based factors, effective integration of sustainability practices into university planning and activities can be achieved. This research contributes to filling the knowledge gap regarding the factors influencing the implementation of sustainability in Saudi Arabian higher education institutions (HEIs). The study emphasizes the importance of addressing organizational structure, decision-making processes, and leadership in order to successfully implement sustainability practices on university campuses.